Peran Diseminasi Teknologi dalam Meningkatkan Pengetahuan Petani dan Produksi Padi di Lahan Rawa Lebak Sumatera Selatan - Syahri Syahri; Renny Utami Somantri; Tumarlan Thamrin (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Syahri S, Somantri RU, Thamrin T. 2019. Dissemination technology to enhance farmers knowledge and rice production in swamps of South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 584-594. Palembang: Unsri Press. The government continues to strive in order to increase rice production, especially in swamps. In fact, at the end of 2018, the Ministry of Agriculture initiated the SERASI program’s. However, adoption of technologies at farmers level are still very slow. So that, South Sumatra AIAT always campaign the good agricultural practices which have been produced by IAARD. It was done to improve the welfare of farmers, especially on swampy. The activity was carried out on 12 farmer groups in Jukdadak village, Tanjung Lubuk subditsrict, distrcit of OKI from May to December 2018. Dissemination of technology is done through several methods, including: 1) making an integrated rice crop management demonstration plot of 5 ha, 2) socialization of 2.5 ha of new rice varities, 3) technology dissemination through farmer training, 4) farmer group meetings, 5) technology demonstrations, and 5) dissemination of dissemination material produced by the IAARD. The technologies which has introduced in demonstration plot includes the Legowo 2:1, the use of adaptive varities (Inpari 30 and Inpari 43), fertilization based on the results of soil test kit and pest control based on IPM principles, 21 days seedling, making local microorganism (MOL) and the use of leaf chart and PUTR. The parameters analyzed included the growth and rice yield on both of demonstration plot and display, increasing farmers' knowledge, and increasing rice productivity. The results show that rice productivity at the demonstration plot location and varities socialization averaged 4.8 t/ha (Inpari 30) and 4.0 t/ha (Inpari 43). The technology dissemination was able to increase rice productivity at the assisting location, which reached 19.1% compared to the previous year. In addition, an increase in farmers' knowledge in carrying out rice cultivation, especially in the swampy swamp land.Keywords: technology dissemination, farmers knowledge, rice production, swamp, Sumatera Selatan